Genome wide analysis of NLP transcription factors reveals their role in nitrogen stress tolerance of rice - Jagadhesan, B.; Sathee, Lekshmy; Meena, Hari S.; Jha, Shailendra K.; Chinnusamy, Viswanathan; Kumar, Arvind; Kumar, Santosh (Springer, 2020)
The NIN-LIKE PROTEIN (NLP) family of transcription factors were identified as nitrate-responsive cis-element (NRE)-binding proteins, which function as transcriptional activators in the nitrate-regulated expression of downstream genes. This study was aimed at genome-wide analysis of NLP gene family in rice and the expression profiling of NLPs in response to nitrogen (N) supply and deficiency in rice genotypes with contrasting N use efficiency (NUE). Based on in silico analysis, 6 NLP genes (including alternative splice forms 11 NLPs) were identified from rice. Expression of NLPs was promoted by nitrate supply as well as N deficiency (NLP1, NLP3, NLP4 and NLP5). Four rice genotypes APO (high NUE under sufficient N), IR83929-B-B-291-3-1-1 (IR-3-1-1), Nerica-L-42 (NL-42) (High NUE at low N), and Pusa Basmati 1 (PB1, low NUE) to correlate traits governing NUE and expression of NLPs. Analysis of rate of nitrate uptake and expression of N assimilatory and uptake genes established that IR-3-1-1 has high uptake and assimilation efficiency, translating into high NUE, whereas PB1 is efficient in uptake only when N availability is high. Along with the transcriptional upregulation of NLPs, genotype IR-3-1-1, displayed highest expression of OsNRT1.1B gene, the closest rice homologue of nitrate transceptor AtNRT1.1 and plays major role in nitrate uptake, translocation and signaling in rice. The results showed that high NUE rice genotypes has both high Nitrogen uptake efficiency (NUpE) and Nitrogen utilization efficiency (NUtE), resulting from the effective and coordinated signal transduction network involving the rice homologue of nitrate transceptor OsNRT1.1B, the probable primary nitrate response (PNR) regulator OsNLP1 and the master response regulator OsNLP3, a homologue of AtNLP6/7.